Uncovering more than a decade of WEAI use in USAID projects - Moore, Lindsey; Dissanayake, Madhu; Malapit, Hazel J.; Go, Ara (International Food Policy Research Institute, 2023)
Since its launch in 2012, the Women’s Empowerment in Agriculture Index (WEAI) has been widely used in USAID projects to prioritize and target activities that aim to promote women’s empowerment. It has been implemented in at least 37 countries by more than 200 partners and 60 different USAID operating units, offering valuable insights into the gender dynamics of agricultural production and identifying opportunities to enhance gender equality and women’s empowerment. By providing a more nuanced understanding of the challenges that women encounter in the agricultural sector, WEAI has played a crucial role in enhancing the ability of USAID programming to improve the lives of women and their families. This report presents key findings gathered from all reported WEAI use cases in the Development Experience Clearinghouse (DEC), the largest resource for USAID-funded technical and project materials. A use case refers to a unique, real-world ex ample in which WEAI has been applied or utilized. A use case can demonstrate how WEAI has been used in a specific context or project, providing insight into its effectiveness, limitations, and potential for future applications. Together, these findings highlight the importance of WEAI as a tool for promoting gender equality and empowering women in the agricultural sector, while also providing useful insights that can inform future policies and programs.